Mobility, Kinematic, Singularity, and Workspace Analysis of a Translational Parallel Manipulator with 2(RRPaRR)-PRRR Kinematic Chains - Adriyan Adriyan; Indra Hasan; Deru Assadullah Assadullah Hanif; Daniel Rumahorbo; Bima Amrianto; Rahmad Illahiy (Politeknik Negeri Lhokseumawe, 2023)
This article presents an asymmetric parallel manipulator with 2(RRPaRR)-PRRR kinematic chains. This manipulator aims to operate as a lower-mobility parallel manipulator with the pure translational motion of its platform. Therefore, a series of analyses are performed to fulfill this intention. First, the mobility analysis is performed by applying the Grübler-Kutzbach equation and the screw theory. Then, the kinematic, singularity, and workspace analysis are applied to analyze this PM. As a result, the application of the screw theory for the configuration of its kinematic chains shows its mobility in a pure translational motion in space. Then, this manipulator has a closed-form solution for its direct kinematic problem expressed in a quadratic equation. By applying singularity and workspace analysis via visualization, the singularity-free workspace along the z-axis of its workspace can be identified. This can later be used as a useful workspace. Overall, the presented manipulator can be applied to a translational parallel manipulator